(untitled) (Medico Legal Update, 2021)
Background: Candida species are part of the normal oral microbiota being Candida albicans. Objective: This study was designed and carried out to find the effect of laser on Candida albicans bacterial cell line. Materials and Method: 16 mice 2 months ages which divided into 4 groups each one consist of 4 mice, while additional 4 mice (group E) were not exposed to the laser beam and considered as a control while the other groups were irradiated with laser beam after anaesthetized and swapped by the species on the tongue of target animal with range of 250 clinical isolates of Candida species, the groups were exposed for different time 10, 15, 20, and 25 seconds (groups A, B, C, and D respectively) with a duration of 2 hours. Results: The no. of colony/2cm2 were calculated for four times and there mean was calculated, the means were 109, 107, 104, and 102 , for groups A, B, C, and D respectively, while it was 1015 in control group. Conclusions: Laser beam reached the tissue of the cervical lymph nodules that treated with laser, the electromagnetic oscillations gradually “swing and excite “single cells, this thought to eventually intensify the bionomical process that ultimately regulate the performance of various vital organs.